2021
DOI: 10.1007/s11071-021-06784-7
|View full text |Cite
|
Sign up to set email alerts
|

Impact of information diffusion on epidemic spreading in partially mapping two-layered time-varying networks

Abstract: We propose a new epidemic model considering the partial mapping relationship in a two-layered time-varying network, which aims to study the influence of information diffusion on epidemic spreading. In the model, one layer represents the epidemic-related information diffusion in the social networks, while the other layer denotes the epidemic spreading in physical networks. In addition, there just exist mapping relationships between partial pairs of nodes in the two-layered network, which characterizes the inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(12 citation statements)
references
References 48 publications
(52 reference statements)
0
9
0
Order By: Relevance
“…Later works observed that, apart from information diffusion, epidemic transmission is influenced by other factors, including network topology, heterogeneity in individual activity levels, and the adoption of immune behavior. Among these factors, the heterogeneity of individual activity levels has attracted extensive attention from scholars and yielded some interesting insights [27,28]. For example, Liu et al [29] investigated the dynamic propagation process in complex networks with active nodes.…”
Section: Introductionmentioning
confidence: 99%
“…Later works observed that, apart from information diffusion, epidemic transmission is influenced by other factors, including network topology, heterogeneity in individual activity levels, and the adoption of immune behavior. Among these factors, the heterogeneity of individual activity levels has attracted extensive attention from scholars and yielded some interesting insights [27,28]. For example, Liu et al [29] investigated the dynamic propagation process in complex networks with active nodes.…”
Section: Introductionmentioning
confidence: 99%
“…These models have various useful applications in real-world situations and can suggest effective and suitable strategies to control the spreading of rumors. It is important to note that rumors are often spread in community and social networks; hence, there is a high similarity between the spreading of rumors and the transmission of infectious diseases (see, for instance, [13][14][15]).…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [5] presented a new epidemic model in multiplex networks to investigate the impact of positive and negative preventive information on epidemic spreading. Considering the partial mapping relationship in a two-layered time-varying network, Guo et al [6] proposed a novel epidemic model to study the impact of information diffusion on epidemic propagation. Zeng et al [7] identified the super communicators by studying the dynamic mechanism of information-disease coupling.…”
Section: Introductionmentioning
confidence: 99%